Biaxially oriented composite material and application thereof
By introducing acrylic grafted polypropylene and alumina nanosheets into the bidirectional tensile polypropylene matrix, a composite material of composite grafted polypropylene and alumina nanosheets is formed, which solves the electrical strength reduction and dielectricity after the introduction of inorganic nanofillers. The problem of increased losses has achieved excellent effects of high breakdown field strength and film formation.
Patent Information
- Application Number
- CN202411557960.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the prior art, when inorganic nanofillers are introduced into the bidirectional tensile polypropylene matrix, filler agglomeration is prone to occur, resulting in problems such as decreasing electrical strength, increasing leakage current, and increasing dielectric loss, which in turn limits the nanocomposite modification method. application.
Using composite grafted polypropylene as masterbatch, combined with alumina nanosheets as inorganic phase, the introduction of acrylic grafted polypropylene and the orientation arrangement of alumina nanosheets form a bidirectional bidirectional with high breakdown field strength and excellent film formation. Stretch composite material.
The breakdown field strength is significantly improved, the energy storage density is improved, and the dielectric loss is maintained, achieving coordinated modulation of the film formation properties and energy storage density of polypropylene matrix composite materials.
Smart Images

Figure CN119391077A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials and relates to a biaxially stretched composite material and application thereof. Background Art
[0002] A large number of studies have shown that the introduction of inorganic nanofillers into the polypropylene matrix can significantly improve the dielectric constant and breakdown field strength of the composite material, thereby playing a role in improving the energy storage density. However, for the modification of biaxially oriented polypropylene, the introduction of inorganic particles will cause serious filler agglomeration, decreased electrical strength, increased leakage current, and increased dielectric loss. In addition, the poor compatibility between rigid inorganic particles and polymer materials causes problems such as interface discontinuity and inability to stretch into film, which in turn limits the further application of nanocomposite modification methods in polypropylene matrices.
[0003] Therefore, there is an urgent need to solve the problem of coordinated modulation of film-forming properties and energy storage density of polypropylene matrix composites. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a polypropylene-based biaxially oriented composite material with high breakdown field strength and excellent film-forming property and application thereof.
[0005] Specifically, the purpose of the present invention is to provide the following aspects:
[0006] On the one hand, a biaxially oriented composite material is provided, wherein the composite material uses composite grafted polypropylene as a masterbatch and aluminum oxide nanosheets as an inorganic phase.
[0007] Wherein, the composite grafted polypropylene takes polypropylene as a matrix.
[0008] The composite grafted polypropylene has acrylic acid grafted polypropylene as an organic composite phase.
[0009] Wherein, the composite material has a grafted carbonyl group.
[0010] In a second aspect, a method for preparing the composite material according to the first aspect is provided, the method comprising:
[0011] Step 1, preparing aluminum oxide nanosheets and acrylic acid grafted polypropylene respectively;
[0012] Step 2, reacting the aluminum oxide nanosheets, acrylic acid grafted polypropylene and polypropylene pellets to obtain the composite material.
[0013] In step 2, the reaction comprises:
[0014] Step 2-1, melt blending the acrylic acid grafted polypropylene and polypropylene pellets to obtain composite grafted polypropylene;
[0015] Step 2-2, melt-blending the composite grafted polypropylene and the aluminum oxide nanosheets for a second time to obtain the composite material.
[0016] In a third aspect, a biaxially stretched composite film is provided, wherein the composite film is made of the biaxially stretched composite material described in the first aspect.
[0017] Wherein, the composite film uses a biaxially stretched composite material as a filler.
[0018] Wherein, the dielectric constant of the composite film is between 2.35 and 2.41.
[0019] In a fourth aspect, a method for preparing the composite film described in the third aspect is provided, the method comprising: using a biaxially oriented composite material as a filler and a polyimide film as a mold, and preparing the composite film by hot pressing and biaxially oriented.
[0020] The beneficial effects of the present invention include:
[0021] (1) The biaxially oriented composite material provided by the present invention has polypropylene as a matrix, acrylic acid grafted polypropylene as an organic composite phase, and aluminum oxide nanosheets as an inorganic phase. The composite of the three takes into account the characteristics of biaxial stretchability. The introduction of acrylic acid grafted polypropylene and the directionally arranged aluminum oxide nanosheet structure significantly improve the breakdown field strength, obtain a higher energy storage density than that of polypropylene monomer material, and maintain a lower dielectric loss.
[0022] (2) In the biaxially stretched composite material provided by the present invention, the alumina nanosheets are sintered by a step-wise method to prevent the intermediate product from breaking during the rapid heating process, thereby obtaining a complete nanosheet structure.
[0023] (3) The preparation method of the biaxially stretched composite material provided by the present invention is simple and easy to implement, and is easy to promote and apply in industry, which is of great significance in the capacitor field.
[0024] (4) The biaxially oriented composite film provided by the present invention has uniform thickness and uniform film formation; the dielectric constant is between 2.35 and 2.41, the dielectric loss is kept at the order of 1E-3, the breakdown field strength reaches 860 to 870 kV / mm, and the energy storage density reaches 7.8 to 8.0 J / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0025] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only used for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work.
[0026] In the attached picture:
[0027] FIG1 (a) shows the TEM characterization of the γ-alumina nanosheets prepared in Example 1;
[0028] FIG1( b ) shows the TEM characterization of the γ-alumina nanosheets prepared in Comparative Example 1;
[0029] Figure 2 A comparison chart of dielectric constants and material loss spectra of biaxially stretched composite films prepared in Example 1, Comparative Example 2 and Comparative Example 3 is shown;
[0030] Figure 3 A comparison diagram of the DC breakdown Weibull distribution of the biaxially stretched composite films obtained in Example 1, Comparative Example 2 and Comparative Example 3 is shown;
[0031] Figure 4 The TEM characterization of the cross section of the biaxially stretched composite film prepared in Example 1 is shown;
[0032] Figure 5 The infrared spectrum of the biaxially stretched composite material prepared in Example 1 is shown;
[0033] Figure 6 A comparison diagram of the thickness distribution of the biaxially stretched composite films prepared in Example 1, Comparative Example 2 and Comparative Example 3 is shown;
[0034] Figure 7 A frequency domain spectrum comparison diagram of the dielectric constant and dielectric loss tangent of the biaxially stretched composite films prepared in Examples 1-4 is shown;
[0035] Figure 8 A comparison diagram of the breakdown field intensity distribution of the biaxially stretched composite films prepared in Examples 1-4 is shown;
[0036] FIG9 (a) shows a breakdown field strength diagram of the biaxially stretched composite film obtained in Example 1;
[0037] FIG9( b ) shows the breakdown field strength diagram of the biaxially stretched composite film prepared in Comparative Example 1. DETAILED DESCRIPTION
[0038] The following will refer to the attached Figure 1(a) to Figure 9(b)Specific embodiments of the present invention are described in more detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0039] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0040] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "rear", etc. indicate positions or positional relationships based on the working state of the present invention, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0041] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.
[0042] On the one hand, according to the biaxially stretched composite material provided by the present invention, the composite material uses composite grafted polypropylene as a masterbatch and uses aluminum oxide nanosheets as an inorganic phase.
[0043] Furthermore, the alumina nanosheets are γ alumina nanosheets.
[0044] Among them, gamma alumina is a transitional alumina with an amorphous to microcrystalline structure and generally has a higher specific surface area.
[0045] Furthermore, the composite grafted polypropylene takes polypropylene as a matrix and acrylic acid grafted polypropylene as an organic composite phase.
[0046] According to a preferred embodiment, the composite material comprises the following components in parts by weight:
[0047] Polypropylene 90-110 parts;
[0048] Acrylic acid grafted polypropylene 90-100 parts;
[0049] 0.5~2 parts of alumina nanosheets.
[0050] In the present invention, the introduction of acrylic acid grafted polypropylene and the directional arrangement of aluminum oxide nanosheet structure significantly improve the breakdown field strength.
[0051] In a further preferred embodiment, the composite material comprises the following components in parts by weight:
[0052] Polypropylene 100-105 parts;
[0053] Acrylic acid grafted polypropylene 95-100 parts;
[0054] 1~1.5 parts of alumina nanosheets.
[0055] In a further preferred embodiment, the composite material comprises the following components in parts by weight:
[0056] Polypropylene 100 parts;
[0057] 100 parts of acrylic acid grafted polypropylene;
[0058] 1 part of alumina nanosheets.
[0059] According to the present invention, the composite material has a -1 The presence of the grafted carbonyl group also indicates that acrylic acid grafted polypropylene was successfully introduced into the composite material.
[0060] In the present invention, the aluminum oxide nanosheets are prepared by a step sintering method to prevent the intermediate product from breaking during the rapid heating process, thereby obtaining a complete nanosheet structure. Preferably, the aluminum oxide nanosheets are prepared by the following steps:
[0061] Step 1-1, pretreating a soluble aluminum salt to obtain a weakly acidic solution;
[0062] Step 1-2, heat-treating the weakly acidic solution, washing and drying to obtain a product to be treated;
[0063] Step 1-3, sintering the product to be treated stepwise to obtain the alumina nanosheets.
[0064] In step 1-1, the pretreatment includes: dissolving a soluble aluminum salt in water, and then adjusting the pH with a weak base.
[0065] In step 1-1, the soluble aluminum salt is selected from one of aluminum carbonate, aluminum acetate, and aluminum sulfate 18hydrate powder, preferably aluminum sulfate 18hydrate powder.
[0066] The soluble aluminum salt can easily form a solution in water, which is beneficial to the subsequent steps. Aluminum sulfate 18hydrate powder is usually of high purity and contains fewer impurities, which is helpful for preparing high-purity aluminum oxide nanosheets; more importantly, the crystal water in aluminum sulfate 18hydrate powder can be released during the heat treatment process, which is helpful for forming porous aluminum oxide nanosheets.
[0067] In step 1-1, in order to uniformly dissolve the soluble aluminum salt in water, stirring is performed at a rate of 1000-2000 r / min for 1-5 h; preferably, stirring is performed at a rate of 1400-1600 r / min for 2-4 h; for example, stirring is performed at a rate of 1500 r / min for 3 h.
[0068] In step 1-1, since soluble aluminum salts are usually highly acidic, a weak base is usually used to adjust the pH to 4.8~5.1, such as 5.0. At this time, the soluble aluminum salt forms an aluminum hydroxide precursor suspended in the water liquid, that is, the weakly acidic solution obtained at this time is a suspension; if the pH is greater than 7, a rod-shaped material will be obtained.
[0069] Furthermore, the weak base is helpful for adjusting pH and in order to avoid the introduction of impurity ions, ie, to be removed in the subsequent steps, the weak base is preferably aqueous ammonia.
[0070] In step 1-2, the aluminum hydroxide precursor formed in step 1-1 is converted into aluminum oxide through heat treatment.
[0071] In step 1-2, the heat treatment temperature is 180-200°C, and the time is 18-36 hours; preferably, the heat treatment temperature is 185-195°C, and the time is 24-38 hours; for example, the heat treatment temperature is 190°C, and the time is 24 hours.
[0072] Under these conditions, aluminum oxide nanosheets with a sheet-like structure can be obtained.
[0073] In step 1-2, the heat-treated material is preferably washed with water until it becomes neutral, so as to remove impurities, unreacted weak base such as ammonia water, and impurities soluble in water.
[0074] In step 1-2, freeze drying is preferably used to remove moisture, and the product obtained by freeze drying is purer.
[0075] Furthermore, the freeze drying time is not too demanding, as long as the water is removed. Usually the freeze drying time is 12 to 24 hours, and 12 hours is usually sufficient.
[0076] In step 1-2, the heat treatment is preferably carried out in a high pressure reactor.
[0077] In step 1-3, the step sintering includes: heating from room temperature to 140-160°C at a heating rate of 5-20°C / min, and keeping the temperature for 1-4 hours; then heating to 500-700°C at a heating rate of 5-20°C / min, and keeping the temperature for 2-3.5 hours; and then naturally cooling to room temperature.
[0078] The inventors have found that step sintering can prevent the product from being broken due to too fast a temperature rise.
[0079] In a further preferred embodiment, the step sintering includes: heating from room temperature to 145-155°C at a heating rate of 8-12°C / min, and keeping warm for 2-3 hours; then heating to 550-650°C at a heating rate of 8-12°C / min, and keeping warm for 2.5-3 hours; and then naturally cooling to room temperature.
[0080] In a further preferred embodiment, the step sintering includes: heating from room temperature to 150°C at a heating rate of 10°C / min, and keeping warm for 3 hours; then heating to 600°C at a heating rate of 10°C / min, and keeping warm for 3 hours; and then naturally cooling to room temperature.
[0081] In steps 1-3, the step sintering is preferably performed in an inert gas atmosphere such as nitrogen.
[0082] In the present invention, the acrylic acid grafted polypropylene is obtained by modifying polypropylene with acrylic acid. Preferably, the acrylic acid grafted polypropylene is obtained by the following steps:
[0083] Step 1-1', dissolving polypropylene pellets in an organic solvent to obtain a first solution;
[0084] Step 1-2', adding acrylic acid to the first solvent to obtain a second solution;
[0085] Step 1-3', adding the initiator solution into the second solvent, and successively filtering and extracting to obtain acrylic acid-grafted polypropylene.
[0086] In step 1-1', the organic solvent is preferably selected from one or more of decahydronaphthalene, toluene and xylene, preferably xylene.
[0087] The organic solvent is used to dissolve the polypropylene pellets for grafting reaction. Xylene can also be used as a solvent for the initiator to help the initiator be evenly dispersed in the reaction system.
[0088] In step 1-1', the mass ratio of the polypropylene pellets to the volume ratio of the organic solvent (g:mL) is 3:(90-150), preferably 3:(95-110), for example 3:100.
[0089] Among them, the solubility of polypropylene pellets in organic solvents is limited, so more organic solvents are needed to ensure that the polypropylene pellets can be fully dissolved. Too much organic solvent may reduce the reaction rate of the reaction system.
[0090] In step 1-1', polypropylene pellets are dissolved in an organic solvent and fully dissolved at 90-110°C, such as 100°C.
[0091] The polypropylene in the polypropylene pellets is a non-polar polymer, and its solubility in organic solvents increases with increasing temperature. Within the temperature range of 90-110°C, it is sufficient for polypropylene to be fully dissolved in organic solvents.
[0092] In step 1-2', acrylic acid is added to the first solvent at 70-80°C, such as 80°C.
[0093] Among them, acrylic acid has a high reactivity in the temperature range of 70~80℃, and can effectively undergo free radical graft polymerization reaction with polypropylene; and can avoid adverse consequences such as runaway polymerization caused by over-rapid reaction.
[0094] In step 1-2', the ratio (g:mL) of polypropylene pellets to acrylic acid solution is 1:0.05-0.5, preferably 1:0.1-0.2, for example 1:0.17. Under this condition, acrylic acid is easy to polymerize with polypropylene.
[0095] In step 1-3', the initiator solution is prepared by dissolving the initiator in an organic solvent to obtain a mixed solution with a concentration of 20-30%, and then adding the mixed solution to the second solution; for example, an initiator solution with a concentration of 25% is obtained, and then the initiator solution is added to the second solution; the organic solvent at this time is preferably consistent with the organic solvent selected when the polypropylene pellets are dissolved in the organic solvent in step 1-1', for example, both are xylene.
[0096] Furthermore, the initiator is dibenzoyl peroxide or dicumyl peroxide, preferably dibenzoyl peroxide.
[0097] Among them, dibenzoyl peroxide has a moderate effective catalytic period as an initiator and performs well in the polypropylene grafting reaction. The reaction conditions are milder than those of diisopropylbenzene peroxide. Within a reaction time of 2 hours, the cleavage effect on the polypropylene molecular chain is weak.
[0098] In step 1-3', the temperature when the initiator solution is added is not higher than the boiling point of acrylic acid, which is 70-110°C, such as 80°C.
[0099] In step 1-3', the mass ratio of polypropylene to initiator is 1:0.005-0.25, for example, 1:0.13. Too high an initiator content will cause severe cracking of polypropylene, while too low an initiator content will lead to inadequate reaction and low grafting rate.
[0100] In step 1-3', the initiator solution is added to the second solvent and reacted for 6 to 10 hours, for example, 8 hours, to allow the reaction to proceed fully.
[0101] In step 1-3', acetone is preferably used for suction filtration. Acetone has a relatively high volatility, which is conducive to rapid removal; and acetone has a high solubility, which can effectively remove residual organic solvents and other organic impurities in polypropylene.
[0102] On the other hand, according to the method for preparing the composite material of the first aspect provided by the present invention, the method comprises:
[0103] Step 1, preparing aluminum oxide nanosheets and acrylic acid grafted polypropylene respectively;
[0104] Step 2, reacting the aluminum oxide nanosheets, acrylic acid grafted polypropylene and polypropylene pellets to obtain the composite material.
[0105] In step 2, the reaction comprises:
[0106] Step 2-1, melt blending the acrylic acid grafted polypropylene and polypropylene pellets to obtain composite grafted polypropylene;
[0107] Step 2-2, melt-blending the composite grafted polypropylene and the aluminum oxide nanosheets for a second time to obtain the composite material.
[0108] In step 2-1, the primary melting temperature is 170° C. to 220° C., preferably 185° C. to 200° C., for example, 200° C. Within this temperature range, polypropylene is fully melted, has strong fluidity, and will not cause thermal degradation.
[0109] In step 2-1, the primary melting time is 10 to 20 minutes, preferably 15 minutes. The primary melting time is sufficient to ensure that the polypropylene is fully melted.
[0110] In step 2-2, the secondary melting temperature is 185° C. to 195° C., for example, 185° C. This temperature should be lower than the primary melting temperature but higher than its melting point.
[0111] In step 2-2, the secondary melting time is 10 to 20 minutes, preferably 15 minutes, so that the composite material is completely mixed.
[0112] In a third aspect, a biaxially oriented composite film is provided according to the present invention. The composite film uses a biaxially oriented composite material as a filler and a polyimide film as a mold. The composite film has uniform thickness and uniform film formation. The dielectric constant is between 2.35 and 2.41, the dielectric loss is maintained at the order of 1E-3, the breakdown field strength reaches 860 to 870 kV / mm, and the energy storage density reaches 7.8 to 8.0 J / cm 3 The dielectric constant is between 2.35 and 2.41.
[0113] In one embodiment, the dielectric constant is as high as 2.41, the dielectric loss is kept at the order of 1E-3, the breakdown field strength is 864 kV / mm, and the energy storage density is 7.96 J / cm 3 .
[0114] In a fourth aspect, according to the method for preparing the composite film of the third aspect provided by the present invention, the method comprises: using a biaxially oriented composite material as a filler and a polyimide film as a mold, and preparing the composite film by hot pressing and biaxially oriented.
[0115] In the present invention, the polyimide film should have an appropriate thickness and size so as to completely wrap the biaxially oriented composite material in the subsequent hot pressing process, and the thickness is usually selected to be 100-150 μm.
[0116] In the present invention, the temperature of hot pressing is 190-230°C, the time is 15-20 minutes, and the pressure is 20-30 MPa; for example, the temperature is 200°C, the time is 18 minutes, and the pressure is 25 MPa. Under the above hot pressing parameters, the biaxially oriented composite film can be fully melted, formed, and fixed.
[0117] In the present invention, the stretching temperature is 150-170°C, and the rate is 90-110 mm / s; for example, the stretching temperature is 160°C, and the rate is 100 mm / s. Under this stretching parameter, the biaxially stretched composite film has moderate fluidity and is conducive to stretching.
[0118] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.
[0119] Example 1
[0120] (1) Preparation of γ-alumina nanosheets:
[0121] 0.05 mol of aluminum sulfate 18hydrate powder was dissolved in 50 mL of deionized water at room temperature and stirred at 1500 r / min for 3 h; then the pH value of the solution was adjusted to 5 with ammonia water and stirred with a stirring rod for 30 min to obtain a suspension;
[0122] The suspension was transferred to a 100 mL stainless steel autoclave with a Teflon liner and subjected to hydrothermal treatment at 190°C for 24 h. The obtained product was then separated by filtration and washed with deionized water until neutral, and freeze-dried for 12 h to obtain a white product.
[0123] The obtained white product was placed in a muffle furnace with a nitrogen atmosphere, and the temperature was increased from room temperature to 150°C at a heating rate of 10°C / min and kept at this temperature for 3 h; then the temperature was increased to 600°C at a heating rate of 10°C / min and kept at this temperature for 3 h; then the product was naturally cooled to room temperature to obtain γ-alumina nanosheets.
[0124] The obtained γ-alumina is shown in Figure 1 (a), which shows that its structure is relatively regular and the edges are clear.
[0125] (2) Preparation of acrylic acid grafted polypropylene:
[0126] 60 g of polypropylene pellets were dissolved in 2000 mL of xylene at 100° C. to obtain a first solution; the temperature was lowered to 80° C., 10 mL of acrylic acid was added dropwise, and the mixture was stirred evenly to obtain a second solution; dibenzoyl peroxide was added to xylene to obtain a mixed solution with a dibenzoyl peroxide concentration of 25%, 32 mL of the mixed solution was added to the second solution, and the reaction was carried out for 8 h. Stirring and nitrogen atmosphere were maintained throughout the reaction. After the reaction was completed, the obtained product was poured into acetone for suction filtration, and extracted in a deionized water environment for 24 h using a Soxhlet extractor to obtain 56 g of acrylic acid-grafted polypropylene.
[0127] (3) 15 g of acrylic acid grafted polypropylene and 15 g of polypropylene were melt-blended at 200 °C for 15 min to obtain 30 g of composite grafted polypropylene; the obtained 30 g of composite grafted polypropylene was melt-blended with 0.15 g of γ-alumina nanosheets at 185 °C for 15 min to obtain a biaxially stretched composite material.
[0128] (4) using a circular cutter with a diameter of 50 mm, a plurality of circular holes with a diameter of 5 cm were cut out on a first polyimide film with a thickness of 100 μm, a second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film, 0.2 g of the biaxially oriented composite material was placed in the circular hole of the first polyimide film, a third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it, and then a flat plate vulcanizer was used for hot pressing treatment, the temperature was set to 200 °C, the pressure was set to 25 MPa, the processing time was set to 18 mins, the exhaust times were set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a composite polypropylene casting sheet;
[0129] The composite polypropylene cast sheet was biaxially stretched at a temperature of 160°C and a rate of 100 mm / s to obtain a biaxially stretched composite film.
[0130] Figure 4 The TEM characterization of the cross-section of the prepared biaxially stretched composite film is shown, and it can be seen that the effective biaxial stretching causes the directional arrangement of the nanosheets, and the directional arrangement of the nanosheets effectively suppresses the electric field distortion and hinders the development of the electrical breakdown path, thereby leading to an increase in the breakdown field strength.
[0131] Figure 5 The infrared spectrum of the biaxially oriented composite material is shown. It can be seen that at 1712 cm -1 The presence of a grafted group (carbonyl group, derived from the grafted acrylic acid group) at the position of the polypropylene copolymer proves that the acrylic acid grafted polypropylene proposed in the present invention is successfully introduced into the composite system.
[0132] Example 2
[0133] (1) preparing γ-alumina nanosheets in the same manner as in Example 1;
[0134] (2) preparing acrylic acid grafted polypropylene in the same manner as in Example 1;
[0135] (3) 15 g of acrylic acid grafted polypropylene and 15 g of polypropylene were melt-blended at 200 °C for 15 min to obtain 30 g of composite grafted polypropylene; the obtained 30 g of composite grafted polypropylene was melt-blended with 0.3 g of γ-alumina nanosheets at 185 °C for 15 min to obtain a biaxially stretched composite material.
[0136] (4) using a circular cutter with a diameter of 50 mm, a plurality of circular holes with a diameter of 5 cm were cut out on a first polyimide film with a thickness of 100 μm, a second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film, 0.2 g of the biaxially oriented composite material was placed in the circular hole of the first polyimide film, a third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it, and then a flat plate vulcanizer was used for hot pressing treatment, the temperature was set to 200 °C, the pressure was set to 25 MPa, the processing time was set to 18 mins, the exhaust times were set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a composite polypropylene casting sheet;
[0137] The composite polypropylene cast sheet was biaxially stretched at a temperature of 160°C and a rate of 100 mm / s to obtain a biaxially stretched composite film.
[0138] Example 3
[0139] (1) preparing γ-alumina nanosheets in the same manner as in Example 1;
[0140] (2) preparing acrylic acid grafted polypropylene in the same manner as in Example 1;
[0141] (3) 15 g of acrylic acid grafted polypropylene and 15 g of polypropylene were melt-blended at 200 °C for 15 min to obtain 30 g of composite grafted polypropylene; the obtained 30 g of composite grafted polypropylene was melt-blended with 0.9 g of γ-alumina nanosheets at 185 °C for 15 min to obtain a biaxially stretched composite material.
[0142] (4) using a circular cutter with a diameter of 50 mm, a plurality of circular holes with a diameter of 5 cm were cut out on a first polyimide film with a thickness of 100 μm, a second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film, 0.2 g of the biaxially oriented composite material was placed in the circular hole of the first polyimide film, a third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it, and then a flat plate vulcanizer was used for hot pressing treatment, the temperature was set to 200 °C, the pressure was set to 25 MPa, the processing time was set to 18 mins, the exhaust times were set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a composite polypropylene casting sheet;
[0143] The composite polypropylene cast sheet was biaxially stretched at a temperature of 160°C and a rate of 100 mm / s to obtain a biaxially stretched composite film.
[0144] Example 4
[0145] (1) preparing γ-alumina nanosheets in the same manner as in Example 1;
[0146] (2) preparing acrylic acid grafted polypropylene in the same manner as in Example 1;
[0147] (3) 15 g of acrylic acid grafted polypropylene and 15 g of polypropylene were melt-blended at 200 °C for 15 min to obtain 30 g of composite grafted polypropylene; the obtained 30 g of composite grafted polypropylene was melt-blended with 1.5 g of γ-alumina nanosheets at 185 °C for 15 min to obtain a biaxially stretched composite material.
[0148] (4) using a circular cutter with a diameter of 50 mm, a plurality of circular holes with a diameter of 5 cm were cut out on a first polyimide film with a thickness of 100 μm, a second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film, 0.2 g of the biaxially oriented composite material was placed in the circular hole of the first polyimide film, a third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it, and then a flat plate vulcanizer was used for hot pressing treatment, the temperature was set to 200 °C, the pressure was set to 25 MPa, the processing time was set to 18 mins, the exhaust times were set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a composite polypropylene casting sheet;
[0149] The composite polypropylene cast sheet was biaxially stretched at a temperature of 160°C and a rate of 100 mm / s to obtain a biaxially stretched composite film.
[0150] Comparative Example 1
[0151] Comparative Example 1 is a non-optimized preparation scheme for γ-alumina nanosheets, and the preparation of the biaxially stretched composite film is the same as that of Example 1. The specific technical scheme is as follows:
[0152] (1) Preparation of γ-alumina nanosheets:
[0153] 0.05 mol of aluminum sulfate 18hydrate powder was dissolved in 50 mL of deionized water at room temperature and stirred at 1500 r / min for 3 h; then the pH value of the solution was adjusted to 5 with ammonia water and stirred with a stirring rod for 30 min to obtain a suspension;
[0154] The suspension was transferred to a 100 mL stainless steel autoclave with a Teflon liner and subjected to hydrothermal treatment at 190°C for 24 h. The obtained product was then separated by filtration and washed with deionized water until neutral, and freeze-dried for 12 h to obtain a white product.
[0155] The obtained white product was placed in a muffle furnace with a nitrogen atmosphere, and the temperature was increased from room temperature to 600°C at a heating rate of 10°C / min and kept at this temperature for 3 h; then the product was naturally cooled to room temperature to obtain γ-alumina nanosheets.
[0156] (2) Preparation of acrylic acid grafted polypropylene:
[0157] 60 g of polypropylene pellets were dissolved in 2000 mL of xylene at 100° C. to obtain a first solution; the temperature was lowered to 80° C., 10 mL of acrylic acid was added dropwise, and the mixture was stirred evenly to obtain a second solution; dibenzoyl peroxide was added to xylene to obtain a mixed solution with a dibenzoyl peroxide concentration of 25%, 32 mL of the mixed solution was added to the second solution, and the reaction was carried out for 8 h. Stirring and nitrogen atmosphere were maintained throughout the reaction. After the reaction was completed, the obtained product was poured into acetone for suction filtration, and extracted in a deionized water environment for 24 h using a Soxhlet extractor to obtain 56 g of acrylic acid-grafted polypropylene.
[0158] (3) 15 g of acrylic acid grafted polypropylene and 15 g of polypropylene were melt-blended at 200 °C for 15 min to obtain 30 g of composite grafted polypropylene; the obtained 30 g of composite grafted polypropylene was melt-blended with 0.15 g of γ-alumina nanosheets at 185 °C for 15 min to obtain a biaxially stretched composite material.
[0159] (4) using a circular cutter with a diameter of 50 mm, a plurality of circular holes with a diameter of 5 cm were cut out on a first polyimide film with a thickness of 100 μm, a second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film, 0.2 g of the biaxially oriented composite material was placed in the circular hole of the first polyimide film, a third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it, and then a flat plate vulcanizer was used for hot pressing treatment, the temperature was set to 200 °C, the pressure was set to 25 MPa, the processing time was set to 18 mins, the exhaust times were set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a composite polypropylene casting sheet;
[0160] The composite polypropylene cast sheet was biaxially stretched at a temperature of 160°C and a rate of 100 mm / s to obtain a biaxially stretched composite film.
[0161] FIG1 (a) shows the TEM characterization of the γ-alumina nanosheets prepared in Example 1, and FIG1 (b) shows the TEM characterization of the γ-alumina nanosheets prepared in Comparative Example 1. It can be clearly seen that the γ-alumina nanosheets prepared in Example 1 have a complete structure, which is due to the step sintering method that prevents the intermediate product from breaking during the rapid heating process, thereby obtaining a complete nanosheet structure.
[0162] Comparative Example 2
[0163] In Comparative Example 2, unmodified polypropylene pellets were used to prepare a biaxially oriented composite film, and the specific technical scheme is as follows:
[0164] A circular cutter with a diameter of 50 mm was used to cut a number of circular holes with a diameter of 5 cm on a first polyimide film with a thickness of 100 μm, a second polyimide film with a thickness of 100 μm was placed at the bottom of the first polyimide film, 0.2 g of polypropylene pellets were placed in the circular holes of the first polyimide film, a third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it, and then a flat plate vulcanizer was used for hot pressing treatment, the temperature was set to 200° C., the pressure was set to 25 MPa, the treatment time was set to 18 min, the exhaust times were set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a polypropylene casting sheet;
[0165] The polypropylene cast sheet was biaxially stretched at a temperature of 160°C and a rate of 100 mm / s to obtain a biaxially stretched composite film.
[0166] Comparative Example 3
[0167] Comparative Example 3: A biaxially oriented composite film was prepared using pure polypropylene as the organic phase and γ-alumina nanosheets as the inorganic phase. The specific technical scheme is as follows:
[0168] (1) Preparation of γ-alumina nanosheets:
[0169] 0.05 mol of aluminum sulfate 18hydrate powder was dissolved in 50 mL of deionized water at room temperature and stirred at 1500 r / min for 3 h; then the pH value of the solution was adjusted to 5 with ammonia water and stirred with a stirring rod for 30 min to obtain a suspension;
[0170] The suspension was transferred into a 100 mL stainless steel autoclave with a Teflon liner and subjected to hydrothermal treatment at 190°C for 24 h. The obtained product was then separated by filtration and washed with deionized water until neutral, and freeze-dried for 12 h to obtain a white product.
[0171] The obtained white product was placed in a muffle furnace with a nitrogen atmosphere, and the temperature was increased from room temperature to 150°C at a heating rate of 10°C / min and kept at this temperature for 3 h; then the temperature was increased to 600°C at a heating rate of 10°C / min and kept at this temperature for 3 h; then the product was naturally cooled to room temperature to obtain γ-alumina nanosheets.
[0172] (2) 15 g of polypropylene pellets and 0.15 g of γ-alumina nanosheets were melt-blended at 180 °C for 15 min to prepare a composite material.
[0173] (3) Using a circular cutter with a diameter of 50 mm, a plurality of circular holes with a diameter of 5 cm were cut out on a first polyimide film with a thickness of 100 μm, a second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film, 0.2 g of the composite material was placed in the circular hole of the first polyimide film, a third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it, and then a flat plate vulcanizer was used for hot pressing treatment, the temperature was set to 200 °C, the pressure was set to 25 MPa, the processing time was set to 18 mins, the exhaust times were set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a composite polypropylene casting sheet;
[0174] The composite polypropylene cast sheet was biaxially stretched at a temperature of 160°C and a rate of 100 mm / s to obtain a biaxially stretched composite film.
[0175] Figure 2 The frequency domain spectrum comparison diagram of the dielectric constant and dielectric loss tangent of the biaxially stretched composite film prepared in Example 1, Comparative Example 2 and Comparative Example 3 shows that the dielectric constant of the biaxially stretched composite film prepared in Example 1 is 2.41, the dielectric constant of the biaxially stretched composite film prepared in Comparative Example 2 is 2.2, and the dielectric constant of the biaxially stretched composite film prepared in Comparative Example 3 is 2.3. It is obvious that the dielectric constant of the biaxially stretched composite film prepared in Example 1 is better, and it is improved by 9.5% compared with the biaxially stretched composite film prepared in Comparative Example 2. The dielectric loss of the biaxially stretched composite film prepared in Example 1 is kept at the order of 1E-3.
[0176] Figure 3 The DC breakdown Weibull distribution comparison diagram of the biaxially stretched composite films obtained in Example 1, Comparative Example 2 and Comparative Example 3 is shown. It can be seen that the breakdown field strength of the biaxially stretched composite film obtained in Example 1 is the best, reaching 864 kV / mm, which is 1.5 times that of the biaxially stretched composite film obtained in Comparative Example 2, achieving a significant improvement in the breakdown field strength. Compared with Comparative Example 3, the breakdown field strength is increased by 240 kV / mm. After testing, the characteristic energy storage density of the biaxially stretched composite film obtained in Example 1 reached 7.96 J / cm 3 .
[0177] Figure 6 The thickness distribution comparison diagram of the biaxially stretched composite films prepared in Example 1, Comparative Example 2 and Comparative Example 3 is shown. The thickness of three different samples was measured 15 times at different positions to characterize the thickness uniformity of the materials. It can be seen that the biaxially stretched composite film prepared in Example 1 has a thickness close to that of the biaxially stretched composite film prepared in Comparative Example 2, which is 10 microns; while the biaxially stretched composite film prepared in Comparative Example 3 has poor thickness dispersion, uneven film formation, and poor film forming properties.
[0178] Figure 7 The frequency domain spectra of the dielectric constant and dielectric loss tangent of the biaxially stretched composite films prepared in Examples 1 to 4 are shown. The comparison shows that with the increase of the content of the inorganic phase γ-alumina nanosheets, the dielectric constants of Examples 1, 2, 3, and 4 increase significantly; on the other hand, the introduction of inorganic particles leads to a significant increase in low-frequency conductivity loss, with the maximum order of magnitude reaching 0.04, which exceeds the usable range of film capacitors.
[0179] Figure 8 The comparison diagram of the breakdown field strength distribution of the biaxially stretched composite films prepared in Examples 1 to 4 is shown. The comparison shows that with the increase of the content of the inorganic phase γ-alumina nanosheets, the breakdown field strength shows a downward trend, and the effect of improving the breakdown field strength by introducing the low content (0.5wt%) of the inorganic phase γ-alumina nanosheets in Example 1 is the most significant.
[0180] FIG9 (a) shows a breakdown field strength diagram of the biaxially stretched composite film prepared in Example 1; FIG9 (b) shows a breakdown field strength diagram of the biaxially stretched composite film prepared in Comparative Example 1. By comparison, it can be seen that the improvement in the breakdown field strength of the biaxially stretched composite film prepared in Example 1 is relatively obvious, which is due to the regular nanosheet structure.
[0181] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.
Claims
1. A biaxially stretched composite material, characterized in that: The composite material uses composite grafted polypropylene as a masterbatch and aluminum oxide nanosheets as an inorganic phase.
2. The composite material according to claim 1, characterized in that Preferably, the composite grafted polypropylene is based on polypropylene.
3. The composite material according to claim 1, characterized in that The composite grafted polypropylene uses acrylic acid grafted polypropylene as an organic composite phase.
4. The composite material according to claim 1, characterized in that A grafted carbonyl group exists in the composite material.
5. A method for preparing the composite material according to claim 1, characterized in that: The method comprises: Step 1, preparing aluminum oxide nanosheets and acrylic acid grafted polypropylene respectively; Step 2, reacting the aluminum oxide nanosheets, acrylic acid grafted polypropylene and polypropylene pellets to obtain the composite material.
6. The method according to claim 5, characterized in that In step 2, the reaction comprises: Step 2-1, melt blending the acrylic acid grafted polypropylene and polypropylene pellets to obtain composite grafted polypropylene; Step 2-2, melt-blending the composite grafted polypropylene and the aluminum oxide nanosheets for a second time to obtain the composite material.
7. A biaxially oriented composite film, characterized in that: The composite film adopts the biaxially oriented composite material described in claim 1.
8. The composite film according to claim 7, characterized in that: The composite film uses a biaxially stretched composite material as a filler.
9. The composite film according to claim 7, characterized in that: The dielectric constant of the composite film is between 2.35 and 2.
41.
10. A method for preparing the composite film according to claim 7, characterized in that: The method comprises: using a biaxially stretched composite material as a filler and a polyimide film as a mold, and preparing the composite film through hot pressing and biaxial stretching.
Citation Information
Patent Citations
Method for preparing polypropylene / nano composite dielectric with high direct current breakdown field strength
CN107163401A
Compound dielectric material of alternating multilayer structure and production method of compound dielectric material of alternating multilayer structure
CN110722854A
High-temperature-resistant polypropylene composite dielectric material based on oil-phase Al2O3 nanocrystals and preparation method of high-temperature-resistant polypropylene composite dielectric material
CN117264254A
Ternary composite all-organic polypropylene-based high-energy-storage-density composite material and preparation method thereof
CN117447791A
High-performance biaxial orientation polypropylene-based capacitor film and preparation method and application thereof
CN118206787A